Using Solar Thermal Energy in the Sludge Drying Process of a Wastewater Treatment Plant A case study of Kattastrand WWTP in Härnösand, Sweden - Svensson, Isak (Chalmers tekniska högskola / Institutionen för arkitektur och samhällsbyggnadsteknik (ACE), 2021)
Wastewater sludge is produced wherever humans live and is one of the final fractions of conventional wastewater treatment. The wastewater sludge is commonly used in agriculture as a fertilizer, disposed in landfills, incinerated or used for plant soil production but this varies by country and region based on legislation, management trends and regional conditions. Newly proposed legislation in Sweden suggests a ban on the use of wastewater sludge in agriculture as it contains pollutants that could pose a risk for the environment and human health. In combination with the suggested ban a requirement for phosphorus recycling is suggested as wastewater sludge contain lots of nutrients that otherwise would be lost. The public inquiry suggests two technology chains for the new management that is required and in both these technology chains sludge drying is a key a process. Thermal sludge drying is also a recommended hygiene treatment method and will result in more efficient transportation due to volume and mass reduction of the sludge. But as thermal drying requires large amounts of energy it is essential to evaluate sustainable sludge drying alternatives to be able to meet commitments regarding greenhouse gas emissions. This thesis is evaluating the potential of using solar thermal energy in the sludge drying process and is designed as a case study for a specific wastewater treatment plant in Härnösand in northern Sweden. Feasibility is evaluated by conducting a cost-benefit analysis for the identified scenarios and compared with the zero alternative which is the current management for the specific treatment plant. The results show large potential in using solar thermal energy in sludge drying but due to large emissions related to the intermediate sludge storage required since solar energy is only available during the summer in Sweden the most profitable alternative is to have multiple energy sources to be able to conduct continuous operation of the drying process. The results in this thesis should be viewed as ...